2018
DOI: 10.1007/s10995-018-2586-y
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in the Utilization of Infertility Services: A Focus on American Indian/Alaska Natives

Abstract: Objectives Previous studies have identified racial/ethnic disparities in infertility care, but patterns among American Indian/Alaska Natives (AI/AN) have not been reported. Our objective was to evaluate infertility services use in the US by race/ethnicity using data from the National Survey of Family Growth (NSFG). Methods We analyzed female respondent data from the pooled NSFG cycles 2002, 2006-2010 and 2011-2013. Respondents reported use of infertility services and types of services. We calculated weighted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…Humphries et al [ 13 ] cited that race and ethnicity, especially Blacks, were strong predictors of poorer outcomes on ART treatment. A racial and ethnic difference in pregnancy rates following intrauterine insemination (ART) was also observed to be lower among American AIAN (prevalence PPR 0.60, 95% CI 0.43–0.83) and Black (PPR 0.53, 95% CI 0.44–0.63) compared to White women in a study by Craig et al [ 22 ] and Janitz et al [ 17 ]. Also, a reduced ART service utilization was also observed for Hispanic women compared to non-Hispanic women as observed by Janitz et al [ 17 ] in a binary racial/ethnic perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humphries et al [ 13 ] cited that race and ethnicity, especially Blacks, were strong predictors of poorer outcomes on ART treatment. A racial and ethnic difference in pregnancy rates following intrauterine insemination (ART) was also observed to be lower among American AIAN (prevalence PPR 0.60, 95% CI 0.43–0.83) and Black (PPR 0.53, 95% CI 0.44–0.63) compared to White women in a study by Craig et al [ 22 ] and Janitz et al [ 17 ]. Also, a reduced ART service utilization was also observed for Hispanic women compared to non-Hispanic women as observed by Janitz et al [ 17 ] in a binary racial/ethnic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A racial and ethnic difference in pregnancy rates following intrauterine insemination (ART) was also observed to be lower among American AIAN (prevalence PPR 0.60, 95% CI 0.43–0.83) and Black (PPR 0.53, 95% CI 0.44–0.63) compared to White women in a study by Craig et al [ 22 ] and Janitz et al [ 17 ]. Also, a reduced ART service utilization was also observed for Hispanic women compared to non-Hispanic women as observed by Janitz et al [ 17 ] in a binary racial/ethnic perspective. Dimitriadis et al [ 23 ] concluded that race affects timely access to infertility care, diagnosis, and treatment cycle, having some racial groups waiting significantly longer prior to seeking evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators found that each non-White group-Black, Hispanic, and other race-was more likely to have infertility than White women. However, all non-White groups were much less likely to receive fertility treatment-Black women were most significantly impacted and were 29% less likely to report ever having received fertility treatment (19) The most recent studies evaluated the NSFG data including responses from the 2002, 2006-2010, and 2011-2013 surveys and broadened the typical racial categories by additionally including American Indian/Alaskan Natives (AI/ANs) women (22,23). Black women had a 1.45 times greater prevalence of infertility than White women.…”
Section: Disparities In Access To Infertility Carementioning
confidence: 99%
“…According to their analysis, Indigenous women experienced 1.37 times greater prevalence of infertility compared to White women. Though Indigenous women face increased rates of infertility, very little research attends to the particular barriers they face in accessing fertility care (Janitz et al, 2019). To our knowledge there is also no research exploring this topic for non-federally recognized tribes.…”
Section: Introductionmentioning
confidence: 99%